A Social Engineering Mitigation Model Based on Digital Security Literacy for Social Media Users in Indonesia - Diana Novita; Hanifah Hanifah; Agus Herwanto (Asosiasi Pengelola Jurnal Informatika dan Komputer Indonesia, 2026)
The development of digital technology and the increasing use of social media in Indonesia have expanded people's communication activities, but have also increased the risk of security attacks based on human manipulation or social engineering. These attacks exploit user behavioral weaknesses rather than technical system vulnerabilities, thus posing a significant threat in the modern information security ecosystem. This study aims to develop a social engineering mitigation model based on digital security literacy to increase social media user awareness. The research method uses a quantitative approach with a survey technique of 210 respondents who are active social media users in Indonesia. Data were analyzed using Structural Equation Modeling–Partial Least Square (SEM-PLS) to examine the relationship between digital security literacy, cybersecurity awareness, and user vulnerability to social engineering attacks. The results show that digital security literacy significantly increases user awareness (β = 0.71; p < 0.001) and can reduce attack vulnerability by 64%. This finding emphasizes the importance of a human-centric cybersecurity approach that places humans as the primary layer of defense in digital security. The proposed mitigation model includes continuous digital security education, increased security awareness, and the implementation of adaptive authentication as a preventive strategy against social engineering attacks. This research provides practical contributions to the development of user behavior-based information security strategies and provides recommendations for educational institutions, organizations, and policymakers in strengthening the digital security resilience of Indonesian society..